Ranking faiths : religious stratification in America - Davidson, James D. (Rowman & Littlefield Publishers, 2011)
Ranking Faiths: Religious Stratification in America discusses how religion shapes access to power, privilege, and prestige in the U.S., both historically and today. James D. Davidson and Ralph E. Pyle dispel the idea that the U.S. was founded on theprinciple of religious equality for all, documenting how religion has been a factor in the allocation of power from the colonial period through the present. From the time of the earliest settlements in America through today, the book demonstrates that some religious groups have had more access to economic, political, and social rewards than others.